АНАЛІТИЧНИЙ РОЗРАХУНОК ЗАСТУПНИМИ СХЕМАМИ МАГНІТНИХ ПОТОКІВ ТА ВТРАТ У МАГНІТНИХ СИСТЕМАХ ШУНТУВАЛЬНИХ РЕАКТОРІВ - Басова, А.В.; Іванков, В.Ф. (Інститут електродинаміки Національної академії наук України, 2023)
For high-voltage shunt reactors with rods with non-magnetic gaps, an analytical method for calculating magnetic fluxes based on substitute circuits has been developed by substantiation by finite element modeling, and the calculation of main and additional losses in magnetic systems has been refined. The results of loss calculations are compared with their estimates during type tests of reactors. Bibl. 11, fig. 7.